2015
DOI: 10.1002/jcsm.12009
|View full text |Cite
|
Sign up to set email alerts
|

Improved body weight and performance status and reduced serum PGE2 levels after nutritional intervention with a specific medical food in newly diagnosed patients with esophageal cancer or adenocarcinoma of the gastro‐esophageal junction

Abstract: BackgroundThe majority of cancer patients loses weight and becomes malnourished during the course of their disease. Metabolic alterations and reduced immune competence lead to wasting and an increased risk of infectious complications. In the present study, the effect of a nutritionally complete medical food, which is high in protein and leucine and enriched with fish oil and specific oligosaccharides, was investigated on immune function, nutritional status, and inflammation in patients with esophageal cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 49 publications
(109 reference statements)
2
40
0
1
Order By: Relevance
“…In line, oral commercial nutritional supplementation in 92 patients with advanced NSCLC undergoing paclitaxel and cisplatin/carboplatin treatment (29) resulted in a greater energy and protein intake and muscle gain, and lower values for fatigue, loss of appetite and neuropathy than in the control group who received an isocaloric diet. A positive effect of oral nutritional intervention on body weight and muscle mass during chemotherapy or concurrent chemo-radiotherapy in cancer was also observed by us and others in the past years (29-36) ( Table 2 ). Some evidence exists that surgery does not hamper the anabolic response to feeding in cancer as shown by the improved leucine balance to a commercial amino acid infusion in cancer patients within 48 hours of undergoing colorectal surgery (37).…”
Section: Introductionsupporting
confidence: 75%
“…In line, oral commercial nutritional supplementation in 92 patients with advanced NSCLC undergoing paclitaxel and cisplatin/carboplatin treatment (29) resulted in a greater energy and protein intake and muscle gain, and lower values for fatigue, loss of appetite and neuropathy than in the control group who received an isocaloric diet. A positive effect of oral nutritional intervention on body weight and muscle mass during chemotherapy or concurrent chemo-radiotherapy in cancer was also observed by us and others in the past years (29-36) ( Table 2 ). Some evidence exists that surgery does not hamper the anabolic response to feeding in cancer as shown by the improved leucine balance to a commercial amino acid infusion in cancer patients within 48 hours of undergoing colorectal surgery (37).…”
Section: Introductionsupporting
confidence: 75%
“…A four-week intervention in esophageal cancer patients administered ONS containing leucine and fish oil significantly improved body weight change (p < 0.05) and Eastern Cooperative Oncology Group (ECOG) score (p < 0.05) [24]. Similarly, nutritional intervention significantly reduced weight loss in head and neck cancer patients (p = 0.024) [25].…”
Section: Resultsmentioning
confidence: 99%
“…Patients who received EN containing arginine, n-3 fatty acid, ribonucleic acid, and MCT showed lower serum IL-8 concentration compared to that in the control patients [31]. ONS containing leucine, and fish oil resulted in decreased serum prostaglandin E2 (PGE 2 ) concentrations [24]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, dietary supplementation with n-3 fatty acids including fish oil or marine phospholipids has stabilized loss and appetite observed in patients with cancer cachexia in a randomized controlled double-blinded trial (23). Additionally, other studies have also shown the effectiveness of nutritional supplementations with fish oil or leucine to improve cachexic status in patients with esophagus cancer (24). It could, therefore, be said that dietary supplementation with n-3 fatty acids may be applied to prevent advancing cancer cachexia and decreased quality of life for patients with diagnosed elevated serum AA / EPA or n-6 / n-3 ratio.…”
Section: Discussionmentioning
confidence: 99%